2014
DOI: 10.1038/tp.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Identifying rare variants for genetic risk through a combined pedigree and phenotype approach: application to suicide and asthma

Abstract: Suicidal behavior is a complex disorder, with evidence for genetic risk independent of other genetic risk factors including psychiatric disorders. Since 1996, over 3000 DNA samples from Utah suicide decedents have been collected and banked for research use through the Utah Medical Examiner. In addition, over 12 000 Utah suicides were identified through examination of death certificates back to 1904. By linking this data with the Utah Population Database, we have identified multiple extended pedigrees with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Such a restrictive approach was used as a way of minimizing false positives, even at the risk of having false negatives. For example, there were genes on each of the two lists, from AP and DE analyses, that had clear prior evidence for involvement in suicidality, such as OLR1 10 , 11 (32%) and LEPR 1 , 12 (32%) for AP, and OPRM1 13 , 14 (32%) and CD24 1 , 11 (33%) from DE, but were not included in our subsequent analyses because they did not meet our a priori set 33.3% threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Such a restrictive approach was used as a way of minimizing false positives, even at the risk of having false negatives. For example, there were genes on each of the two lists, from AP and DE analyses, that had clear prior evidence for involvement in suicidality, such as OLR1 10 , 11 (32%) and LEPR 1 , 12 (32%) for AP, and OPRM1 13 , 14 (32%) and CD24 1 , 11 (33%) from DE, but were not included in our subsequent analyses because they did not meet our a priori set 33.3% threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic vulnerability is a well‐studied risk factor for suicide (Brent & Melhem, ; McGuffin, Marusic, & Farmer, ; Pedersen & Fiske, ), with the potential to identify at‐risk cohorts (McGowan et al., ). As part of our own study, the Utah OME has been collecting DNA on suicide completers for over 20 years, and this work has begun to identify specific genetic mutations that may increase suicide risk (Coon et al., ; Darlington et al., ). Given the interesting age, gender, and diagnostic differences discovered in our data, we hope to further refine our genetic studies on youth suicide completers.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal immune activation with the TLR3 agonist poly I:C during mid-pregnancy increases anxiety- and depressive-like behaviors. A genome-wide association study identified TLR3 as genetic risk factor for suicide in individuals with asthma and with a familial risk for asthma (Darlington et al 2014 ). A postmortem study identified abnormal TLR3 over-expression in the dorsolateral prefrontal cortex of 22 depressed suicide victims (Pandey et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%